Estudo da absorção de energia de para-raios de ZnO instalados em linhas de transmissão de 138 kV - Rodrigo de Oliveira Pedrosa (2013)
Zinc Oxide (ZnO) line arresters are usually installed along overhead transmission lines to improve their lightning performance, particularly in areas with very high soil resistivity and intense lightning activity. For lines rated below 230 kV, this technique has proven to be very effective. However, there are few conclusive studies on the energy absorption capability of the ZnO arresters. Due to the probabilistic nature of lightning parameters, the arresters are subjected to different amounts of energy which may excessively stress them. The present study initially investigates the influence of lightning current parameters and the transmission line modeling on the evaluation of the energy absorption capability of the arresters. The energy absorbed by the surge arresters when lightning strokes a 138 kV transmission line is calculated. A statistical analysis of the energy levels is performed using an interactive routine developed using ATP and MATLAB. Two different scenarios are considered: arresters installed in all phases of the tower stricken by lightning, and arresters installed in all phases of every line tower. The results show the importance of using a correct model to study the ZnO surge arresters energy capability. Furthermore, the study shows that Class 2 arresters, generally installed along 138 kV transmission lines, are subjected to energy levels well below their capacity, suggesting that there is a possibility of using Class 1 arresters instead, which would lead to a reduced cost of the line protection project.